REALISASI RENCANA PERTUMBUHAN: BAGAIMANA PERUSAHAAN MEMBIAYAI PERTUMBUHAN - Rosita Widjojo (Bina Ekonomi, 2004)
Companies are grooming themselves for growth and plan to spend aggressively in certain key areas that support that growth. Certain key areas that are the focus of growth are information technology (IT spending), increase in marketing/advertising/sales budget, new product launch and acquisition. To finance these spending, companies will primarily use internal cash and bank financing.